Determinants of newborn care at home among the parents attending maternal and child health clinic in maternity hospital, Thapathali, Kathmandu, Nepal - Shakya, J (Journal of Chitwan Medical College, 2017)
Maternal and child health reveals the basic status of women and child in Nepal. High Infant Mortality rate and Neonatal Mortality rates reveal the inadequate health care delivery and inadequate knowledge and practice of traditional birthing practice and newborn care at home in rural areas. This study was conducted to identify the various determining factors affecting care of the newborn babies at home. A convenient purposive sampling technique was used for the purpose. The leaflets regarding newborn care and common health problems and their management were also distributed to the parents as they needed. The data were collected from 100 parents attending MCH clinic Maternity Hospital, Thapathali by using the semi structured questionnaire consisting of socio-demographic characteristics, knowledge and practice related to care and common health problems of the newborn baby. The obtained data were analyzed by using frequency, percentage, mean value, standard deviation and calculation of P value. This study revealed that the majority (88%) of the literate respondents were from the urban area. 71.42% of the respondents had knowledge about the management of difficulty breathing at home delivery situation. All the respondents fed colostrum and 86% of them had their baby exposed to sun in the morning for about 1-2 hours and 57% had knowledge of common health problems like poor sucking, eye infection and cord infection. The scoring of the knowledge shows that 33% of respondents had adequate knowledge and only 9% had inadequate knowledge of care of the newborn. On the practice side, 33% of the respondents had inadequate practice and only 15 % had adequate practice. Among the respondents of SLC/campus level 68% had the practice of bath on the 2nd day after birth and 64% of the respondents who were literate/ primary level had practiced of bath to their baby immediately after birth. There is statistically significant association between education level and practice of giving bath, (P Value=0.003). Development of leaflets regarding information of care of the newborn and common heath problems and their management at home situation were necessary to prepare and provide information to the parents.